Produção de milho no verão após cultivo de leguminosas como adubos verdes - Salomão, Gisele Rabelo (2015)
The use of green manure to establish the diversity and balance of the production system is one of the paradigms of modern agriculture. The objective of this study was to evaluate the corn crop production after the legume crop. The species used were lab-lab (Dolichos lablab), estilosantes Campo Grande (Stylosantes capitata + Stylosantes macrocephala), velvet bean (Styzolobium aterrimum) and juncea (Crotalaria juncea), the work was carried out between September 2013 and May 2014, led the field at the Faculty of Agricultural Sciences, University of West Paulista (UNOESTE). Corn was sown in 0.90 m spacing between lines, totaling approximately 50,000 plants per hectare after planting the legumes. The treatments consisted of a witness, and four species of green manure. The experimental design was a randomized block design with split plots and four replications. We evaluated the aerial part of pulses at 90 days for dry matter evaluation and determination of the N total part area. For corn yield was analyzed the stand, plant height, number of ears, grains per spike and weight of a hundred grains. It was found that all pulses contributed to an increase in productivity.